Slipped capital femoral epiphysis with hypopituitarism in adults: A case report and literature review. Issue 51 (23rd December 2021) - Niu, Zhixin; Tang, Jinshuo; Shen, Xianyue; Xu, Shenghao; Zhou, Zhongsheng; Liu, Tong; Zuo, Jianlin
Abstract: Rationale: Slipped capital femoral epiphysis (SCFE) is a common disease in pediatric orthopedics. Most research on SCFE has focused on high-risk groups or the whole population, and studies focusing on adult SCFE patients are rare. In the present study, we report the case of an adult patient with SCFE. Patient Concern: A 37-year-old man presented to our clinic with persistent pain that was poorly localized to both hips, groin regions, and thighs for more than 1 year. Diagnoses: A bilateral hip X-ray examination was performed, and the femoral epiphyses were found to be unfused on both sides. Low levels of growth hormone (GH), insulin-like growth factor-1 (IGF-1), triiodothyronine (T3), thyroxine (T4), follicle-stimulating hormone, luteinizing hormone, estradiol, and testosterone, and high levels of thyroid-stimulating hormone, prolactin, and cortisol. Interventions: Hormone-substitution therapies (levothyroxine sodium to treat hypothyroidism and testosterone enanthate to treat hypogonadism) were prescribed. Total hip arthroplasty was performed to treat femoral epiphysis slippage. Outcomes: After 6 months of postoperative follow-up, the patient's gait improved significantly, and bilateral hip pain was relieved. Lessons: When treating adults with SCFE, clinicians must be alert to endocrine disorders. Comprehensive imaging evaluation is crucial for the accurate diagnosis and selection of an appropriate treatment.